A Metabolomic Strategy to Screen the Prototype Components and Metabolites of Shuang-Huang-Lian Injection in Human Serum by Ultra Performance Liquid Chromatography Coupled with Quadrupole Time-of-Flight Mass Spectrometry. (26th February 2014) - Guo, Mingxing; Zhao, Baosheng; Liu, Haiyu; Zhang, Li; Peng, Long; Qin, Lingling; Zhang, Zhixin; Li, Jian; Cai, Chengke; Gao, Xiaoyan
Abstract : Shuang-huang-lian injection ( SHLI ) is a famous Chinese patent medicine, which has been wildly used in clinic to treat acute respiratory tract infection, pneumonia, influenza, and so forth. Despite the widespread clinical application, the prototype components and metabolites of SHLI have not been fully elucidated, especially in human body. To discover and screen the constituents or metabolites of Chinese medicine in biofluids tends to be more and more difficult due to the complexity of chemical compositions, metabolic reactions and matrix effects. In this work, a metabolomic strategy to comprehensively elucidate the prototype components and metabolites of SHLI in human serum conducted by UPLC-Q-TOF/MS was developed. Orthogonal partial least squared discriminant analysis (OPLS-DA) was applied to distinguish the exogenous, namely, drug-induced constituents, from endogenous in human serum. In the S-plot, 35 drug-induced constituents were found, including 23 prototype compounds and 12 metabolites which indicated that SHLI in human body mainly caused phase II metabolite reactions. It was concluded that the metabolomic strategy for identification of herbal constituents and metabolites in biological samples was successfully developed. This identification and structural elucidation of the chemical compounds provided essential data for further pharmacological and pharmacokinetics study of SHLI .